Spatial and temporal variability in the community structure of fishes and invertebrates of Marudu Bay, Sabah - Cheong, Kai Ching (2018)
Estuaries serve as refuge, foraging, breeding and nursery ground for fishes and invertebrates, securing the fisheries stock as well as maintaining biodiversity. Softbottom substrate contribute to nearly half the area of global estuarine habitats; however studies regarding community structure of this substrate are relatively scarce compared to other estuarine habitats (i.e. mangroves, seagrass) especially in Southeast Asia. The present study was conducted at subtidal flats in Marudu Bay (Sabah, Malaysia), which is now part of Tun Mustapha Park, Malaysia's largest marine park in Malaysia after its' gazettement in 2016. This study aims to (1) determine spatial and temporal species composition and abundance of fishes and invertebrates in estuarine subtidal flats, (2) determine their relationship to environmental conditions, and (3) analyze the population dynamics of dominant and commonly marketed species to understand the status of the fisheries stock. The study sites are located at estuarine subtidal flats of five rivers which flows into the Marudu Bay, namely Matunggong River, Bandau River, Taritipan River, Bengkoka River and Telaga River. Sampling of fishes and invertebrates were conducted monthly from March 2014 until April 2015 using three fishing gears including otter trawl, trammel and cast net. Corresponding environmental variables including water parameters (i.e. salinity, temperature), nutrients (i.e. nitrogen, phosphorus) and sediment quality (i.e. particle size, carbon content) were determined. A total of 138 species of fish and invertebrates were recorded, comprised of 79 fish species and 59 invertebrate species. Fish community was dominated (nearly 90% of total fish abundance) by a small number of species, including pony fish (Eubleekeria jonesi, Secutor megalolepis, Photopectoralis bindus), catfish (Arius venosus) and scad (Alepes djedaba). In terms of invertebrate composition, commercially important crab (i.e. Portunus pe/agicus and Penaeus merguiensis) and jellyfish (i.e. Lobonemoides robustus) were the most commonly recorded. The abundance of two jellyfish species ( L. robutus and Catosty/us townsend1) were recorded as markedly seasonally abundant. The total abundance of fish and invertebrate was significantly higher (p<0.05) from August to April with the highest at nearly 16,000 individual/km2. Notably, the abundance of invertebrates was higher from March to June, with most of the abundance contributed by jellyfish (L. robustus). Diversity was higher at Matunggong and Sandau River with H'>0.68 and J'>0.5 compared to other sites. The population dynamics of six dominant and commonly marketed species was determined. Fishing pressure was observed in ponyfish (£ Jones,) and catfish (A. venosus), where fishing mortality was higher than natural mortality with 0.85 and 0.55 respectively. Increase in total abundance (p=-0.38) and diversity (p=-0.32) was significantly (p<0.05) correlated with lower salinity and temperature, consequently related with higher rainfall. Salinity is believed to be a key factor triggering the seasonal bloom of jellyfish with significant (p<0.05) correlation of 0.6, and high abundance of jellyfish is likely causing higher level of soluble reactive phosphorus (p =0.63). Temporal changes of species aggregation were mainly affected by salinity and temperature, while particle size and sediment nutrients affecting species aggregation in different sites. Estuarine subtidal flats in Marudu Bay was found serving as nursery ground for several commercially important fish species (i.e. Carangidae, Sciaenidae, Polynemidae, Haemulidae), emphasizing the importance of the subtidal flats in terms of biodiversity and productivity. Essential biological, ecological and fisheries information obtained in this study is important in supporting future studies and management planning for Marudu Bay and the newly gazetted Tun Mustapha Park.